A novel tool-path generation method for five-axis flank machining of centrifugal impeller with arbitrary surface blades. (January 2017) - Fan, Hong-Zhou; Wang, Shang-Jin; Xi, Guang; Cao, Yan-Long
The centrifugal impeller with arbitrary surface blades is a very important component in automobile, ships, and aircraft industry, and it is one of the most difficult parts to process. Focusing on the machining efficiency improvement, combining the geometric advantages of ruled surface and arbitrary surface, and utilizing the efficient and accurate advantages of flank machining and point machining, this article presents a novel and targeted tool-path generation method and algorithm for five-axis flank machining of centrifugal impeller with arbitrary surface blades. In light of specific characters of different surfaces, the analyses of two different impeller blades are proposed first, the more characteristic and complex geometrical structures of the arbitrary blade are achieved. In rough machining, an approximate ruled surface blade is obtained, and a simple channel is achieved; the flank milling of the centrifugal impeller with ruled surface blades is achieved relative to the point milling of the centrifugal impeller with arbitrary surface blades; and the triangle tool path planning method is added in this process to save the machining time and cost collectively. Furthermore, in semi-finish machining, the approximate sub-ruled blade surfaces are calculated, and a new flank milling method of the sub-ruled blade surfaces is achieved; a new solution for tool interference is achieved in this process and the generation of non-interference tool paths becomes easy. Machining experiments of two different impellers are presented as a test of the proposed methods.